A law unto itself : how the Ontario Municipal Board has developed and applied land use planning policy - Chipman, John George, 1941- (Institute of Public Administration of Canada series in public management and governance., 2002)
Illuminates OMB practices of overturning municipal land-use planning decisions to impose its own policies, which are generally protective of private interests, and of applying provincial planning policies within the context of its own standards.